Influence of Leadership and Competency Behavior on the Performance of Family Planning Extension - Bambang Nurakhim; Agnes Aryanti Kaesmetan (Eduvest - Journal of Universal Studies, 2021)
"The Influence of Leadership and Competency Behavior on The Performance of Family Planning Extension (PLKB) in the Office of Population Control and Family Planning Karawang Regency". This study aims to determine the influence of Leadership Behavior and Competency on the Performance of Kb Extension. Sampling techniques use total sampling (n = 46), and data analysis techniques using Correlation and Regression with SPSS version 22 programs. The results showed that Leadership Behavior had a positive and significant effect on the Performance of KB Extension (t count = 10.215, p < 0.00). Competency positively and significantly affects the Performance of KB Extension (t count = 2,532, p < 0.015). Leadership and Competency Behavior simultaneously positively and significantly affects the Performance of KB Extension (F count = 94.706, p < 0.00). Contribution of Commitment and Competence to the Performance of KB Extension is shown by adjusted R Square value of 0.701 or (70.1%). The remaining 29.9% is affected by other variables. The implication of this research is that there should be a policy of the head of the Karawang District Office of Population Control and Family Planning in improving the Performance of Kb Extension Workers.